POLIAKRILAT PADA BENANG KATUN SEBAGAI SOLUSI PENENUNAN PADA KONDISI KELEMBABAN RENDAH - Nana Hadiana; - Hendra (Politeknik STTT Bandung, 2025)
Low humidity during weaving processes causes cotton yarns to become brittle and prone to breakage. To address this issue, polyacrylate has been explored as an alternative sizing agent due to its flexibility and high adhesion. This study aims to review the effectiveness of polyacrylate sizing on cotton yarns in dry environments. A narrative literature review was conducted by analyzing ten scientific articles published between 2021 and 2025 from reputable databases. The findings show that polyacrylate can enhance yarn tensile strength by up to 30%, reduce energy consumption, and extend the lifespan of weaving machinery. Moreover, bioactive-based polyacrylate formulations support sustainability through improved biodegradability and environmental friendliness. However, certain formulations still pose compatibility challenges with textile finishing processes, such as reactive dyeing and digital printing. Further reformulation and industrial-scale testing are necessary to ensure both technical performance and ecological safety. This review offers strategic insights into the development of future sizing agents that are adaptive, efficient, and sustainable